CSF and Blood Biomarkers in Neuroinflammatory and Neurodegenerative Diseases: Implications for Treatment. (December 2020) - Gaetani, Lorenzo; Paolini Paoletti, Federico; Bellomo, Giovanni; Mancini, Andrea; Simoni, Simone; Di Filippo, Massimiliano; Parnetti, Lucilla
Abstract : Neuroinflammatory and neurodegenerative diseases are characterized by the interplay of a number of molecular pathways that can be assessed through biofluids, especially cerebrospinal fluid and blood. Accordingly, the definition and classification of these disorders will move from clinical and pathological to biological criteria. The consequences of this biomarker-based diagnostic and prognostic approach are highly relevant to the field of drug development. Indeed, in view of the availability of disease-modifying drugs, fluid biomarkers offer a unique opportunity for improving the quality and applicability of results from clinical trials. Herein, we discuss the benefits of using fluid biomarkers for patient stratification, target engagement, and outcome assessment, as well as the most recent developments in neuroinflammatory and neurodegenerative diseases. Highlights: Cerebrospinal fluid and blood biomarkers allow for identification of early state disease. Fluid biomarkers objectively measure and monitor drug efficacy and disease progression. Baseline biomarker assessment can help stratify patients to provide more homogenous disease phenotypes in clinical trials.